Exploring Authentic Assessment Strategies for EFL Speaking: The Experience of an Indonesian High School Teacher at Senior High School - Anak Agung Ayu Mas Sukmawati; Luh Putu Artini; Putu Suarcaya; Ni Putu Era Marsakawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to explore how an EFL teacher at SMA (SLUA) Saraswati 1 Denpasar designs and implements authentic speaking assessment under Curriculum Merdeka, which emphasizes competency-based and student-centered learning through meaningful real-life tasks. The study also identifies the challenges encountered during the assessment process. Employing a qualitative descriptive design, the research focused on one Grade XI class consisting of 20 students across three classroom meetings. Data were collected through classroom observations and semi-structured interviews with the teacher. The findings reveal that authentic speaking assessment was implemented through real-life-based tasks, including pair interviews, individual presentations, and role-plays on ordering food at a restaurant. These tasks were supported by analytic rubrics assessing fluency, pronunciation, vocabulary, grammar, and confidence. The use of pair work and direct feedback increased students’ engagement and confidence in speaking activities. However, several challenges were identified, including limited instructional time, large class size, limited integration of technology, insufficient formal training in assessment literacy, and limited practical guidance from the curriculum. Despite these constraints, the teacher demonstrated adaptive pedagogical creativity in aligning assessment practices with the principles of Curriculum Merdeka. The study highlights the need for stronger institutional support, professional development, and clearer assessment guidelines to ensure the effectiveness, consistency, and fairness of authentic speaking assessment in Indonesian secondary schools.